The Arp8 and Arp4 module acts as a DNA sensor controlling INO80 chromatin remodeling - Sandipan Brahma (Nature Portfolio, 2018)
INO80 chromatin remodeler plays important roles in transcription, DNA repair, recombination, and heterochromatin maintenance. Here the authors characterise the functional interplay between the actin-related proteins (Arps)  in INO80, showing that Arp8 and Arp4 module sense the DNA length separating nucleosomes and regulate nucleosome remodeling.